(untitled) (Annals of Medical Research, 2021)
Introduction: Crush trauma may be life threating in extremities. Crush syndrome leads to a systemic disorder through muscle cytolysis and the spread of metabolic substance into the circulatory system. In the present study, we summarized the follow-up and treatment of 10 cases with intensive care unit (ICU) crush injury. Materials and Methods: We have analyzed the clinical data of 10 patients with crush injury who were under treatment in the intensive care unit of our clinic. Age, sex, diagnosis, APACHE II score, sepsis, intensive care complications, treatment parameters in intensive care and arterial blood gases parameters, routine blood biochemistry, alanine aminotransferase, lactate dehydrogenase, creatine kinase, creatinine, existence of blood urea nitrogen, urinary protein and severity score of the patients have been recorded. Patients have been closely monitored for symptoms of crush injury, changes, crush area, urination and dangerous complications. Results: The mean age of 10 patients (10 male) was 41.3 ± 8.7 years. APACHE II score was 21,7. 8 out of 10 patients had traumatic shock, one showed acute renal failure and one presented with multiple organ dysfunction syndrome (MODS). In 3 patients presenting the criteria for crush syndrome, the symptoms of extremity distension and sensory function disorder were regulated with rapid surgical operation and hemodialysis, and urination increased, even in some patients, it reached the normal level. Serologic parameters were regulated in most of the patients after application. Amputation was applied to 5 (50%) patients in our group for serious infection and crush. 2 (20%) patients died, one because of MODS and one because of acute renal failure. Conclusion: Early and aggressive resuscitation, emergency treatment and close monitoring of serious complications are of great importance for saving the lives of the patients with crush syndrome under intensive care.